2010
DOI: 10.1111/j.1365-2796.2010.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein lowering with rosuvastatin in the METEOR study

Abstract: ). C-reactive protein lowering with rosuvastatin in the METEOR study. J Intern Med 2010; 268: 155-161.Objectives. In addition to its LDL-C-lowering effects, statin treatment reduces the level of C-reactive protein (CRP). Long-term data on this effect in low-risk populations are limited. Furthermore, whether the CRP reduction is a consequence of LDL-C lowering or occurs independently remains unclear. We studied these aspects in the Measuring Effects on intima media Thickness: an Evaluation Of Rosuvastatin (METE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
(41 reference statements)
2
15
0
Order By: Relevance
“…2E). Heterogeneity affecting MI analysis was resolved excluding trials with the most different effect sizes [28,30] and results were confirmed (RR: 0.894; CI: 0.847 to 0.945; p heterogeneity = 0.152; I 2 : 27.2%; p comparison b 0.001).…”
Section: Outcome Meta-analysismentioning
confidence: 98%
See 4 more Smart Citations
“…2E). Heterogeneity affecting MI analysis was resolved excluding trials with the most different effect sizes [28,30] and results were confirmed (RR: 0.894; CI: 0.847 to 0.945; p heterogeneity = 0.152; I 2 : 27.2%; p comparison b 0.001).…”
Section: Outcome Meta-analysismentioning
confidence: 98%
“…First, we could not find a significant correlation between LDL changes and CV events, that is apparently inconsistent with the well known relationship between these parameters observed from phase III intervention trials. The explanation most likely relies in the inclusion of trials [17,[19][20][21][23][24][25][26][27][28]32,33] that were not aimed to assess reduction of CV events but the changes of surrogate end-points induced by statins over short follow-up. Thus, we cannot exclude that longer duration of follow-up might change the strength of association.…”
Section: Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations